The Educational Value of Hinduism on the Gumi Suda Ceremony at the Birth of the Twin Babies with Different Genders (Case Study at Pakraman Village of Ketewel, Sukawati District, Gianyar Regency) - Asthadi Mahendra Bhandesa; I Gede Putu Darma Suyasa; Ni Wayan Kesari Darmapatni (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
This study aimed to identify the educational values of Hinduism on the Gumi Suda ceremony at the Birth of the twin babies with different genders in Pakraman Village of Ketewel, Sukawati District, Gianyar Regency.  The data were collected by using interviews technique and literatures review. Furthermore, the data were analyzed through data reduction process or chosen according to the purpose of the research. The data analysis process was done continuously during the research from the beginning until the end of the research through the systematic tracking and arranging process of the transcripts of interviews, field notes and other materials. The Findings indicated that some of the educational values of Hinduism on the Gumi Suda ceremony at the birth of the twin babies with different genders in Pakraman Village of Ketewel, Sukawati District, Gianyar Regency are tattwa, ethics, ceremonial, health education and social educational values.